Pengaruh Modal Usaha dan Pemasaran terhadap Pendapatan pada Pedagang Sayur di Pasar Tradisional Kecamatan Kuta Badung - Ni Luh Pitri Yuliani Dewi; I Putu Arya Dharmayasa (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This research aims to find out various things about (1)The influence of business  capital on income among vegetable traders in the traditional market  of Kuta Badung District (2) the influence  of marketing on income among  vegetable traders in the traditional market of Kuta Badung District. (3) the influence of the business capital and the marketing strategy to the income of the vegetable trader  on the traditional market of Kuta Badung District. The population in this study were vegetable traders in the traditional market of Kuta Badung District. The sampling technique used proportional random sampling with a sample size of 100 vegetable traders. Data collection methods used questionnaires and were analyzed using multiple linear regression .The results showed that (1) there is a positive and significant effect of business capital on vegetable traders' income partially, (2) there is a positive and significant effect of marketing on vegetable traders' income partially, (3) business capital and marketing simultaneously have a positive and significant effect on vegetable traders' income.